In silico analysis of bioactive compounds from Strobilanthes crispus as MurE inhibitors in Escherichia coli - Aria Aditama , Yoga; Rakhmawati Afrida , Indah; Munandar, Kukuh; Riyanto (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2025)
Urinary Tract Infection (UTI) is one of the most common infectious diseases, predominantly caused by Escherichia coli. Increasing antibiotic resistance has driven the search for new antibacterial agents from natural sources. This study aims to evaluate the potential of bioactive compounds from Strobilanthes crispus as inhibitors of the E. coli MurE enzyme using an in-silico approach. Molecular docking, toxicity prediction, and pharmacokinetic analysis were performed. The docking results demonstrated that apigenin 7-O-beta-D-glucuronide exhibited the highest binding affinity toward MurE with a binding energy of -9,5 kcal/mol, followed by acteoside (-9,4 kcal/mol) and isoacteoside (-9,2 kcal/mol), outperforming ciprofloxacin (-7,1 kcal/mol). Pharmacokinetic analysis indicated that all tested compounds showed good solubility and acceptable safety profiles, althought they exhibited los gastrointestinal absorption and poor oral bioavailability. These findings suggest that S. crispus bioactive compounds possess promising potential as MurE inhibitors and warrant further optimization and experimental validation as antibacterial candidates against E. coli.